Metáforas de aprendizagem: um olhar sobre narrativas multimodais de aprendizes de língua inglesa - Marina Morena dos Santos e Silva (2013)
This research aims to identify, classify and interpret metaphorical linguistic expressions related to the conceptualization of the process of teaching and learning English in multimodal Language Learning Histories of students from a private school, located in the metropolitan area of Belo Horizonte. By analyzing the metaphorsused by these learners, it is expected not only to provide better understanding of the thoughts, beliefs, desires and distresses of this audience, but also reflective development of teachers and researchers about the process of teaching and learning this language nowadays. This work is a qualitative research based on the analysis of documents. The original materials used for analysis were a set of 64 multimodal Language Learning Histories written by the learners. Considering the nature of the data - narrative texts with multimodal elements - it is important to emphasize that the analysis prioritized not only the verbal metaphors,but also the nonverbal ones present in the images illustrating the histories. Koch and Deetz (1981)s methodology was adopted, which consists of a linguistic analysis of the data. The metaphors found were qualitatively analyzed according to the Conceptual Metaphor Theory (LAKOFF& JOHNSON, 1980), the Conceptual Blending Theory (FAUCONNIER & TURNER, 2002) and the Image Schemas (LAKOFF, 1987), and they were quantitavely organized into four categories, according to the target domains investigated: (1) English language learning (2) English, (3) English language learners, and (4) English language teachers. The results show that the group of learners investigated conceptualizes English learning and English itself as a way to access job market. Language and its learning are, therefore, conceptualized and justified as a way of entering the job market and career advancement. Learners were primarily conceptualized as people who make an effort to learn, whereas teachers were conceptualized as learning promoters. It is undeniable that these learners are aware of the importance of English nowadays, as well as its massive presence. They arealso aware of their active role in the learning process and the cognitive and affective dimensions related to the process of teaching and learning.